Management Strategies for Climate Change Mitigation and Adaptation in Coastal Regions: A Systematic Literature Review - Marcos Filho Lima Bastos; Jordana Marques Kneipp; Clandia Maffini Gomes; Ana Paula Perlin; Roberto Schoproni Bichueti (Coasts)
Background: By 2050, most of the global human population will live in coastal regions, and the climatic impacts on these areas represent a significant concern for governments, private sector companies, and societies. Thus, environmental management of coastal regions plays a central role in the global climate agenda. Methods: The study employed a mixed-methods approach, integrating quantitative and qualitative techniques to conduct a systematic literature review (SLR). This included the construction of networks of related topics, time series analysis, literature mapping, and the identification of research gaps. The databases used were Web of Science, Science Direct, and Scopus. The inclusion and exclusion criteria encompassed articles published between 2014 and 2023, off-topic articles, unavailable articles, or paid access articles. At the end, 96 studies were included in this RSL. Results: The results revealed a predominance of studies addressing climate management in coastal regions, primarily focused on adaptation strategies. However, there is a notable deficiency in studies that address integrated mitigation and adaptation strategies. Time series analysis predicted an increase in the focus on coastal management and climate change in the coming years. Conclusion: The research underscores the central role of coastal management in addressing climate change and achieving the Sustainable Development Goals (SDGs). It encourages multi-level management, integrating government officials, business leaders, and civil society in the development of more effective practices for climate change adaptation and mitigation.